Adapting to climate change: Scenario analysis of grain production in China - Zhou, Shudong; Zhou, Wenkui; Lin, Guanghua; Chen, Jing; Jiang, Tong; Li, Man (Emerald Publishing Limited, 2017)
The purpose of this paper is to examine the impacts of future climate change and the corresponding adaptation activities on grain production and its regional distribution in China.This paper applied the Chinese Agricultural Policy Analysis model, in combination with the findings from agronomic literature with highly detailed agricultural census data, to conduct equilibrium analysis under alternative impact (seasonal drought and climate warming) scenarios and adaptation scenarios (promoting water-saving irrigation, introducing new varieties, and the integrated) associated with climate change.Simulation results indicate that climate change-induced seasonal drought and the resulting yield reduction will incur substantial losses to China’s grain production (by ~8 percent at a national scale). The application of water saving techniques can be an effective solution to seasonal drought. Introducing new varieties will increase the combination of promoting water-saving irrigation and new variety adoption will increase combination of promoting water-saving irrigation and new variety adoption constitute an effective approach to offsetting the negative effects of climate change on grain production.Simulation results indicate that climate change-induced seasonal drought and the resulting sown area reduction will incur substantial losses to China’s grain production by approximately 8 percent, despite farmers’ adaptation activities of switching from water use-intensive crops to drought-tolerant crops to mitigate this negative effect. The application of water saving techniques is an effective solution to seasonal drought; it can lead to a nationwide increase in the sown area by 3.48 percent and in the grain production by 4.15 percent. Introducing new varieties will increase grain outputs and change the spatial distribution of crop production across the country. The combination of promoting water-saving irrigation and new variety adoption will increase the national grain production by 19.6 percent, and thus constitute an effective approach to offsetting the negative effects of climate change on grain production.Results from this study provide practical implications formulate strategies in response to climate change. Central government should reinforce the policies such as new varieties promotion and improve the subsidy method to guide the introduction of new varieties.